Effects of opaR Mutation on the Biological Characteristics and Conjugative Transfer of the Virulence Plasmid of Acute Hepatopancreatic Necrosis Disease-Causing Vibrio parahaemolyticus - Liying WANG; Xuan DONG; Guohao WANG; Dehao WANG; Jingmei XIE; Jingfei LUO; Xianwei WANG; Jie HUANG (Progress in Fishery Sciences, 2024)
Acute hepatopancreatic necrosis (AHPND) is a bacterial disease caused by Vibrio bacteria that severely affects the Pacific white shrimp farming industry. Since AHPND was first identified in China and Vietnam in 2010, it was subsequently identified in Malaysia (2011), Thailand (2012), Mexico (2013), the Philippines (2014), South Korea (2016), Bangladesh (2017), the United States (US) (2017), and Japan (2020). AHPND causes significant economic losses of more than 7 billion US＄ annually to the global shrimp farming industry. It has severely restricted the development of the global shrimp farming industry. Many studies have shown that the pathogens of AHPND are Vibrio spp., including V. parahaemolyticus, V. owensii, V. campbellii, V. harveyi, V. punensis, and V. anguillarum. The virulence of these pathogenic strains was derived from a 70 kb virulent plasmid (pVA1-type plasmid). The pVA1-type plasmid carries pirAB genes encoding the binary toxin pirAB homologous to the insecticidal protein of Photobacterium phosphoreum. The pVA1-type plasmid has been confirmed to carry a novel trb type Ⅳ secretion system (T4SS). Trb-T4SS can mediate the conjugative transfer of the pVA1-type plasmid at high cell density for interspecific horizontal transfer.The quorum sensing (QS) system is also known as the density-sensing system. In the surrounding environment, the QS system allows bacteria to regulate the expression of multiple genes by sensing changes in the concentration of autoinducer signaling molecules. At high cell density, high concentrations of autoinducer signaling molecules bind to receptor proteins to inhibit phosphorylation cascades and high cell density master regulator OpaR is normally expressed. OpaR is involved in the regulation of various biological processes, such as biofilm-forming ability, motility, and the expression of the type Ⅲ and type Ⅳ secretion systems. Reportedly, high concentrations of signaling molecules in the QS system regulate the expression of key genes of the T4SS to increase the conjugative transfer efficiency of drug-resistant plasmids. However, the regulation of the T4SS by opaR in AHPND is not yet reported.In this study, OpaR, the high cell density master regulator of the QS system in V. parahaemolyticus, was selected to explore the relationship between the QS system and T4SS expression, as well as the conjugative transfer of the pVA1-type plasmid. The V. parahaemolyticus 20130629002S01::cat (Vp2S01::cat) strain, a pathogenic strain of AHPND, was used as the starting strain. The opaR gene was replaced with the erythromycin resistance gene (ermB) by homologous recombination and electroporation. The opaR mutant strain (Vp2S01::catΔopaR) was successfully constructed. The effects of OpaR on Vp2S01::cat were explored by performing growth curve and motility assays.Vp2S01::cat and Vp2S01::catΔopaR were cultured continuously for approximately 24 h in a shaking bed at 28 ℃ and 180 r/min. OD600 was measured every 2 h to compare the difference in growth. The results showed that there were no significant differences in the growth curves for Vp2S01::cat and Vp2S01::catΔopaR. Biofilm-forming ability was detected using a crystal violet staining assay. The results showed that the biofilm-forming ability of Vp2S01::catΔopaR was significantly reduced. Growth zone diameter was recorded in 0.3% (swimming) LB agar plates at 28 ℃ for 8 h to analyze the difference in swimming ability. We found that the swimming ability of Vp2S01::catΔopaR increased significantly by 2.67 times compared with that of Vp2S01::cat. Growth zone diameter was recorded in 1.5% (swarming) LB agar plates at 28 ℃ for 12 h to analyze the difference in swarming ability. The results showed that there was no significant difference in swarming ability between Vp2S01::cat and Vp2S01::catΔopaR. However, Vp2S01::catΔopaR had more missing colonies. Using VcLMB29 as the receptor strain, the conjugative transfer efficiency of Vp2S01::cat and Vp2S01::catΔopaR was compared at different time points. We found that the conjugative transfer efficiency of Vp2S01::catΔopaR increased after 12 and 24 h. The conjugative transfer efficiency after 24 h was increased by a factor of 265.43. RNA of Vp2S01::cat and Vp2S01::catΔopaR was extracted after 24 h of conjugative transfer and reverse-transcribed into cDNA for real-time quantitative fluorescence PCR (RT-qPCR). GyrB was used as the reference gene. AphA-qRT, opaR-qRT, and T4SS-qRT primers were used for RT-qPCR. The relative expression levels of genes were calculated using the 2–ΔΔCt method. The results showed that the relative expression levels of T4SS in the Vp2S01::catΔopaR experimental group were significantly increased by 1.13–3.21 times and that the relative expression levels of the key conjugative transfer genes traF, trbE, and traG were significantly increased by 1.96, 1.92, and 3.21 times, respectively.In conclusion, the opaR gene does not affect the growth and swarming motility but does affect the biofilm-forming and swimming ability of Vp2S01::cat. The high cell density master regulator OpaR may affect the conjugative transfer efficiency of the virulent plasmid by regulating the expression levels of T4SS. This study provides fundamental data for analyzing the mechanism by which the QS system regulates the expression of T4SS and the conjugative transfer of the pVA1-type plasmid in AHPND pathogenic bacteria, offering technical support for the control of the horizontal transfer of the virulent plasmid in AHPND-causing bacteria.